INVESTIGATION OF ANTIBACTERIAL PRESCRIBING SITUATIONS IN DENTISTRY FACULTIES AND OTHER DENTAL HEALTH INSTITUTIONS - (:unkn) unknown (NOBEL ILAC, 2017)
Objective: The relationship between the institutions where dentists work and their prescribing performance is not known. This study aimed to investigate antibacterial prescribing practices of dentists working in different healthcare institutions. Material and Method: Dentists' antibacterial-containing prescriptions were analyzed by using Prescription Information System (PIS) of Turkish Medicines and Medical Devices Agency. Distribution of antibacterial-containing prescriptions that were prescribed by dentists in universities and other healthcare institutions, starting from January 2013 for a total of 32 months was examined in terms of diagnosis and time periods. Results: It was found that very few number of antibacterials (n=9,952) were prescribed in dentistry faculties (DF) while most of them (n=13,069,333) were prescribed in other dental health institutions (DHI). In both DF and DHI, the most common prescribed antibacterial group was beta lactam antibacterials-penicillins (93.7% and 71.3%, respectively) and as an antibacterial agent it was amoxicillin + enzyme inhibitors (69.7% and 57.9%, respectively). These were followed by amoxicillin (21.9%) and clindamycin (1.5%) in DF; spiramycin (10.4%) and amoxicillin (9.2%) in DHI. The most frequently prescribed diagnoses were embedded teeth and periapical abscesses-without sinus in DF and DHI, respectively. Conclusion: This study was the first to reveal similar and different aspects of antibacterial prescribing behaviors between the DF and DHI dentists in Turkey. Although preference of the most common drug was similar, detailed examinations showed variations in antibacterial prescribing behaviors of dentists practicing in universities and other institutions.
Keywords: Dentistry; university; dental health institutions; antibacterial; prescribing; CROSS-NATIONAL DATABASE; ANTIBIOTIC USE; PRACTITIONERS; PRESCRIPTION; MANAGEMENT; RESISTANCE; PATTERN; EUROPE